2015
DOI: 10.1002/jso.23914
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and treatment of neck metastases in patients with salivary gland cancers

Abstract: Patients with high-grade cancers should receive END involving levels I-III, whereas patients with node-positive salivary cancers should receive comprehensive TND involving all levels (I-V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 25 publications
6
65
1
Order By: Relevance
“…A study by Han et al reported an occult metastatic rate of 20% among patients with submandibular gland cancer. Most specialists recommend END for all high‐grade tumors, excluding ACC, which is in line with our study because ACCs carried a metastatic rate of only 7%. Hirvonen et al found that 12% of patients with major salivary gland ACC presented with pN+.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A study by Han et al reported an occult metastatic rate of 20% among patients with submandibular gland cancer. Most specialists recommend END for all high‐grade tumors, excluding ACC, which is in line with our study because ACCs carried a metastatic rate of only 7%. Hirvonen et al found that 12% of patients with major salivary gland ACC presented with pN+.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the diagnostics and treatment of salivary gland carcinomas differ from other head and neck carcinomas, of which over 90% are squamous cell carcinomas (SCCs). Mucoepidermoid carcinoma (MEC) and adenoid cystic carcinoma (ACC) are among the most frequent malignancies encountered in the major salivary glands . Treatment recommendations for salivary gland carcinomas are usually based on parotid gland tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether to choose neck dissection for patients with cN0 disease with salivary gland carcinoma is controversial. Patients with high‐grade carcinoma should receive elective neck dissection . Nevertheless, for patients with cN0 disease refusing to receive radical surgery, it was reasonable to detect neck failure during the follow‐up.…”
Section: Discussionsupporting
confidence: 53%
“…On multivariate analysis, lymphovascular invasion was the only prognostic factor for overall survival [1] and was also an independent predictor of recurrence [13,37]. Other tumor-related histologic factors independently associated with decreased survival are perineural involvement of a major nerve [8,24] and solid histological subtype of AdCC [16,17,21,30,35].…”
Section: Incidence and Consequences Of Cervical Lymph Node Metastasismentioning
confidence: 99%